Economic Benefit of New Capacity in the Central Grid - Dalen, Ingar (Institutt for elkraftteknikk, 2009)
Norway and the EU have in recent years established ambitious goals to increase the share of renewable energy in their consumption. On account of these goals, a large-scale wind power development can be expected in northern Norway and Sweden. This development may be financed both by Norway and by countries with less wind resources in order to meet the energy goals imposed upon them. An increased power surplus is dependent on TSOs' abilities to transmit increased amounts of power through the Nordic grid. A scenario of likely power market conditions in year 2025 is used as a basis. The scenario has a high expectancy of new wind power as well as strong grid investments compared to the level in 2009. This thesis assumes an additional increase in annual renewable power production of 22 TWh, divided into 16 TWh in northern Norway and 6 TWh in northern Sweden. Results show that this amount of new power cannot be implemented without large grid investments. The Energy and Power Flow model is utlized to simulate the Nordic power flow for different levels of grid investments. Two grid solutions are proposed that allow the production increase while maintaining an acceptable state of system operation. The first uses DC transmission from Rana to Oslo in order to control power flow through Norway. An additional AC line from Kobbelv to Ritsem allows import from Sweden to the DC line. The second grid solution uses AC line upgrades throughout Norway ensuring two 420 kV lines from Ofoten to Kristiansand. Due to lower impedances in the Swedish grid, a large amount of the Norwegian production flows into and through Sweden. This solution requires a new line from Kobbelv to Ritsem and Rätan to Borgvik in order to solve resulting Swedish transmission congestion. Both grid solutions require a new DC cable from southern Norway to Germany in order to export most of the new power production. These cables require a number of supporting line upgrades in the region. Power producers schedule according to the new market situation, allowing a ...